Gambaran riwayat kejadian diare pada balita dan pelaksanaan PHBS dalam tatanan rumah tangga di Desa Gegelang Kecamatan Manggis tahun 2013 - Dewa Agung Istri Sintha Prajnyaswari; Wayan Citra Wulan Sucipta Putri (DiscoverSys Inc., 2018)
Diarrhea is the second leading cause of death in infants. As one of the disease-based environment, the availability of clean water, sanitation and hygiene is one of the key actors in the incidence of diarrhea. As one of the efforts to improve sanitation and hygiene, health center movement Manggis I community health center develops behaviors of live clean and healthy (PHBS) at the family level. The lowest percentage of households classified by PHBS located in the Gegelang Village which amount is 46%. Among the 10 points PHBS, the cause of diarrhea in infants can be sourced history of exclusive breastfeeding, use of unclean water, the habit of not washing hands with soap and clean water, and does not have healthy latrines. This study was a descriptive cross-sectional study involving seventy-five respondents, i.e. mothers with under five children (12-60 months) in Hamlet Gegelang, Kalanganyar, and Pakel, Gegelang Village. Sampling technique is done by using accidental sampling method. Data collection was conducted using a questionnaire. In this research is found only 13 of 75 (17.3%) of respondents said that the children did not have diarrhea in the last 1 year. A total of 53 respondents (70.7%) said that they did not give exclusive breastfeeding to her child. All respondents had access to clean water, but only 32 of 75 (42.7%) of respondents who process a clean water with appropriate way before drunk. Good hand washing habits only depicted in 30 of 75 (40%) of respondents. Latrine ownership were vary from having latrine with standards compliant (38.7%), have latrine but do not fit to standards-compliant (25.3%), and did not have latrine (36.0%). Conclusion of cross-tabulations showed a trend increase in the number history of diarrhea in under five children on the implementation of PHBS that do not fit to health standards.